European and Islamic trade in the early Ottoman state : the merchants of Genoa and Turkey - Fleet, Kate (Cambridge studies in Islamic civilization., 1999)
By using untapped Latin and Turkish sources, and focusing on the trading partnership between the Genoese and the Turks, Kate Fleet demonstrates how this interaction contributed to the economic development of the early Ottoman state and to Ottoman territorial expansion. Where previous literature has emphasized the military prowess of the early Ottomans and their role as ""the infidel"", this book considers their economic aspirations and their integration into the economy of the Mediterranean basin. This readable, authoritative study illuminates an obscure period in early Ottoman history.